2022
DOI: 10.1021/acsami.2c14799
|View full text |Cite
|
Sign up to set email alerts
|

Iridium Tungstate Nanozyme-Mediated Hypoxic Regulation and Anti-inflammation for Duplex Imaging Guided Photothermal Therapy of Metastatic Breast Tumors

Abstract: Metastasis of breast cancer is key to poor prognosis and high mortality. However, the excess reactive oxygen species (ROS) and inflammatory response induced by photothermal therapy (PTT) further aggravate tumor metastasis. Meanwhile, the hypoxic tumor microenvironment promotes tumor cells to metastasize to distant organs. Herein, the intrinsic limitations of PTT for metastatic tumor have been addressed by fabricating polyethylene glycol modified iridium tungstate (IrWO x -PEG) nanoparticles. The as-designed Ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Since silica-cored Au nanoshells served as the first photothermal nanomaterials for clinical use, more and more inorganic agents with strong absorption in the NIR region, high chemical stability, adjustable water solubility, and minimal cytotoxicity have entered clinical trials. , Clinical trials have also been underway for small organic molecules due to their good biodegradability, good repeatability, and simple preparation. , Nevertheless, the major challenges for the clinical implementation of photothermal nanomaterials are the complex metabolism and excretion behaviors . The representative works on PTT with diverse photothermal nanomaterials in recent years are summarized in Table .…”
Section: Applicationsmentioning
confidence: 99%
“…Since silica-cored Au nanoshells served as the first photothermal nanomaterials for clinical use, more and more inorganic agents with strong absorption in the NIR region, high chemical stability, adjustable water solubility, and minimal cytotoxicity have entered clinical trials. , Clinical trials have also been underway for small organic molecules due to their good biodegradability, good repeatability, and simple preparation. , Nevertheless, the major challenges for the clinical implementation of photothermal nanomaterials are the complex metabolism and excretion behaviors . The representative works on PTT with diverse photothermal nanomaterials in recent years are summarized in Table .…”
Section: Applicationsmentioning
confidence: 99%
“…In addition, it was reported that glycinated and PEGylated ceria nanoparticles exhibited 1.75–1.9 times higher SOD-like activity than uncoated ceria nanoparticles ( Figure 5 b) [ 43 ]. The high physiological stability, biocompatibility, and monodisperisty of nanozymes can be achieved through coating with polyvinylpyrrolidone (PVP) [ 109 ], amine-terminated PAMAM dendrimer [ 110 ], mercaptoundecanoic acid (11-MUA) [ 111 ], PEG [ 112 , 113 ], etc.…”
Section: Manipulation Of Nanozyme Activities For Antioxidant Effectsmentioning
confidence: 99%
“…Cancer is still a serious threat to human health, and its high morbidity and mortality rates have promoted researchers to develop more effective cancer therapies. 1 A variety of emerging cancer therapies including immunotherapy, 2 photothermal therapy (PTT), 3,4 and photodynamic therapy (PDT) 5,6 have been developed. PTT is deemed a most promising tumor treatment method due to its advantages of minimally invasive and localized treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is still a serious threat to human health, and its high morbidity and mortality rates have promoted researchers to develop more effective cancer therapies . A variety of emerging cancer therapies including immunotherapy, photothermal therapy (PTT), , and photodynamic therapy (PDT) , have been developed. PTT is deemed a most promising tumor treatment method due to its advantages of minimally invasive and localized treatment. However, PTT also faces many challenges, including but not limited to the fact that the depth of light penetration is insufficient to completely ablate tumors, the systemic distribution of photothermal conversion agents in the body leads to unnecessary heat damage to normal tissues, and the overexpression of heat shock proteins (HSPs) in cancer cells can greatly reduce the therapeutic effect by increasing the resistance of cells to heat .…”
Section: Introductionmentioning
confidence: 99%